Association Between Hemoglobin A1C and the Severity of Acute Ischemic Stroke in Sudanese Patients in Omdurman Military Hospital - Abdalla Elamin Abdelgadir, Omer; Mahmoud Saeed, Amal; Shadoul Mohamed Farah, Abubaker; Elsebty Mohammed Alhassan Ahmed, Mohanad; Ahmed Osman Farah, Mogahid; Ahmed Abdelhadi Elsayed, Abdelhadi; Abdalhafiz Altahir Ahmedelbasheir, Awab; Saeed Saad Mahgoub, Mahmoud; Khalafalla Mohamed Ahmed, Ahmed (Sudan Journal of Medical Sciences, 2022)
Background: Hemoglobin A1C (HbA1c) levels are known to be linked to a higher risk of stroke. However, no research data is available on the impact of HbA1C on the severity of acute ischemic stroke in Sudan. Methods: This study is a descriptive, cross-sectional hospital-based study of 40 cases of acute ischemic stroke. Ischemic stroke was confirmed using computed tomography (CT) scan at admission; all subjects’ blood HbA1C levels were also measured. Participants were divided into two subgroups based on HbA1C at admission, good glycemic control (GGC) (<7 HbA1C) and poor glycemic control (PGC) (>7 HbA1C), and neurological impairment was assessed using the National Institutes of Health Stroke Scale (NIHSS). Results: The age distribution of the participants was 45-85 years, with an average age of 63.5±9.2 years with the highest frequency (67.5%) in the age group of 55-75 years. PGC had a statistically significant high HbA1C value of 8.9±1.3 (P=0.000), when compared to GGC subgroups 5.1±0. The association between stroke severity and HbA1C levels on admission in this study was statistically significant (P value=0.005), on admission (78.6%) PGC had moderate to severe stroke (> 18.8 NIHSS) versus (33.3%) that of the GGC (>10.4NIHSS). The frequency of elevated HbA1C levels in patients with acute ischemic stroke was 70% in this study. Conclusion: PGC was shown to be linked to the occurrence of stroke and to its severity.